Organizing for Cyber Resilience: Balancing Resilience Paradigms for Sustainable IT Business Value - Van Giel, Ziggy (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
Organizational cyber resilience has been mentioned in literature to take a business-first perspective on ensure both short-term and long-term achievement of business objectives through technology. Nevertheless, it appears that it is still mostly approached from a technical perspective. When a business-first perspective is used, literature makes suggestions that are neither based on theory, nor on empirical findings. By using a design science research approach and relying on a combination of literature, surveys, interviews and case studies, this PhD project aims to develop strategies to achieve organizational cyber resilience by proposing specific organizational capabilities.